Perlindungan Anak dari Bullying di SMP Negeri 14 Kendari: Kajian Maqashid Syariah - Andi Astuti Andi (Institut Agama Islam (IAIN) Kendari, 2025)
This study aims to examine the protection of children from bullying at SMP Negeri 14 Kendari from the perspective of Maqashid Syariah. Bullying in schools can have negative impacts on children’s psychological and social development, making child protection crucial. The perspective of Maqashid Syariah emphasizes the protection of children’s fundamental rights, such as the safety of life, intellect, and dignity. This research employs a qualitative approach, focusing on a case study at SMP Negeri 14 Kendari. Data was collected through interviews with the principal, teachers, and students, as well as document analysis of child protection policies in the school. Thematic analysis was used to analyze the data. The findings indicate that child protection from bullying at SMP Negeri 14 Kendari has been implemented through various character education programs, the creation of a safe environment, and the enforcement of school policies that support students’ well-being. The Maqashid Syariah perspective provides a moral and ethical foundation in addressing bullying cases, focusing on fulfilling the child’s right to live safely and with dignity. Although child protection at the school aligns with the principles of Maqashid Syariah, this study recommends enhancing monitoring and support for victims of bullying. Furthermore, collaboration among the school, parents, and the community should be strengthened to create a safer environment for children. This research offers valuable insights for developing more effective child protection policies in schools.